The Politics of Patronage and the Politics of Kinship: The Meeting of the Ways - Osiek, Carolyn (Biblical theology bulletin, 2009)
Scholarship on patronage in the ancient Mediterranean world abounds but is not unanimous in its understanding of how the patronage system worked, how it was present in the pre-Roman Greek world, and what were the differences, if any, in how it functioned in the Roman West and East. Moreover, little is known about how the system worked among non-elites. In two of Paul's relationships, with Philemon and with Phoebe (Rom 16:1-2), we can see the informal patronage system at work among friends with common community ties.